PENGAWASAN DAN PENGENDALIAN KUALITAS AIR DI KECAMATAN TEMBILAHAN KOTA - Winanda Harvelina; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Indragiri Hilir is a regency which has waters, rivers, swamps, and generally the condition of it’s soil included peat moss. People who live in the area have a problem to get good and clean water condition, also depending with the water from rain to use in dailly activities. However when they are in dry season, they get more difficult for source of clean water. The necessity for clean water make Indragiri Hilir has many water depots as a consequences from increasing of people.The purpose of this research is to know controlling and checking realization for quality water and the factors that can affect Health Department’s effort in Tembilahan City.The Method is used in this research is : location is in Health Department of Indragiri Hilir, Jalan M. Boya No. 07 and refill water depots. Informers included The Chief of Environment Sanitation and staff in Health Problem Restraint Health Department Indragiri Hilir, officer in saniation of UPT Puskesmas Tembilahan City, included Refill Water Depots owners around it.The theory concept is used on this research is controlling and checking realization from Mannulang (2001:184) consists of determining technique and administration standard, do evaluation and scoring also act emendation. This research uses Qualitative Method with data assesment descriptively, in accumulation of data assesment the researcher uses interview sessions, observation, documentation and literatures.The result of this research is to show deficiency of controlling and checking realization Health Department Tembilahan City for clean water because The Implementation is not suitable with set standard, limitedness of humanity resources as sanitatior, facilities, fund, also awareness and knowledge from refill water depot owners can be included as the obstruction factors on realization.Keywords : checking, controlling, refill water depots